Child development - Laleman, Joseph P.; Conrad, Tim; Finzen, Susan (Bloomington : Meridian Education Corporation, 1994)
Contains 5 series of child development from prenatal to eight yers old.
part 1. From prenatal to birth - part 2. From birth to one - part 3. From one to three - part 4. From three to five - part 5. Five to eight.
Executive producer, Twila Sears, Scott Perry ; editor, Richard Webster, Eric Perry ; writer, Jodie S. Kavensky, Joseph P. Laleman, Tim Conrad.
Narrator: Mindy Heusel-Kankel.
System requirements: IBM compatible PC 486/66 processor or better ; 8 MB RAM ; VGA display with 256-color driver and at least 1 MB of VRAM ; local bus PCI video ; sound card ; Audio speakers ; MS Windows 3.1, Windows 95, or Windows NT operating system.
Keywords: Child psychology; Child development; Children -- Growth